SNR-based relay selection in cooperative wireless ad hoc networks. (2018) - Afzal, Muhammad Khalil; Nam, Seung Yeob; Kim, Byung-Seo; Kim, Sung Won
Cooperative communications aim to gain spatial diversity from stations cooperating during data transmission without requiring multiple transceiver antennas on the same station. However, performance from cooperative communications highly depends on the relay-selection method. This paper proposes and evaluates a distributed relay-selection method based on the signal-to-noise ratio of the communication links of candidate relay nodes. A node is selected as a relay node based on the signal-to-noise ratio of its communication link. Moreover, data might be delivered through a relay node that can support high transmission rate rather than through a direct link with a low transmission rate. This paper provides a detailed analysis of the collision probability in the proposed method as compared to a conventional random backoff method. Results demonstrate that the proposed relay-selection method reduces collision probability, and hence, enhances system throughput.